Bridging the gap: barriers to Malaysian public university research commercialisation - Mohamad Sarujee, Siti Manisah; Abdul Ghani Azmi, Ida Madieha; Amid, Azura; Mohamed Sadek, Silmyi (BP Services, 2025)
Introduction: Malaysian public universities achieve only 5-10% downstream commercialisation rates. This compares poorly to 30-60% rates in other Asian economies and developed nations. Current assessment frameworks inappropriately evaluate universities on post-transfer outcomes. These outcomes are beyond their institutional control rather than controllable pre-transfer activities. Methods: This study employed triangulated multi-qualitative analysis. It integrated commercialisation policies from all five Malaysian research universities. The study included comprehensive literature review of six innovation gap clusters and structured interviews with ten Technology Transfer Office (TTO) personnel. The Pre-Transfer Market Readiness Gaps Conceptual Framework applies six complementary theoretical perspectives. This distinguishes controllable pre-transfer activities from uncontrollable post-transfer outcomes. Results: The study validated and extended existing literature by identifying ten critical innovation gaps across three challenge domains that align with six established literature clusters (Strategic/Policy, Skills/Competency, Financial, Organisational/Cultural, Stakeholder Coordination, and Market Orientation). Go-to-market barriers include industry’s lack of R&D adoption readiness (scoring 14.8). Policy framework deficiencies include inadequate commercial viability frameworks (scoring 12.4). Measurement standardisation issues also emerged. Multi-theoretical convergence validates that high-priority gaps operate simultaneously. They span institutional, organisational, resource-based, and relational dimensions identified in prior research. Discussion: The sphere of control analysis reveals important insights. Universities are evaluated against marketing and financial success metrics. These occur beyond their influence. Meanwhile, technical success activities within their control remain inadequately optimised. The performance measurement paradox demonstrates why standardised frameworks produce inconsistent results. There is 5-50% variation when institutions optimise reported performance rather than substantive effectiveness. Conclusion: The study confirms that innovation gaps require integrated multi-theoretical approaches rather than isolated frameworks and contributes both literature validation and a novel paradigm shift toward process-based assessment. This operates within universities’ controllable operational sphere. This enables systematic evaluation of pre-transfer market readiness capabilities whilst maintaining accountability within appropriate institutional boundaries. Future Research: Future studies should develop industry readiness assessment tools, pre-transfer commercial viability frameworks and unified measurement standards that distinguish university-controllable from external factors whilst exploring how the six validated gap clusters evolve through integrated intervention strategies